Equisetum arvense (horsetail) Extract: The First Approved Basic Substance Allowed for EU Crop Protection - Taylor, A.; Bonafos, R.; Chovelon, M.; Parvaud, C. E.; Furet, A.; Aveline, N.; Bertrand, C.; Marchand, P. A. (International Journal of Bio-resource and Stress Management, 2022)
Equisetum arvense is an herbaceous perennial plant traditionally used in human medicine (i.e. for organic silicon supplementation). It is an approved basic substance with fungicidal properties under Article 23 of agricultural EU pesticide regulation (EC) No 1107/2009 (Anonymous, 2009) since 2014 and in Organic Production since 2016. Currently, its approved uses are for arboriculture, horticulture, ornamentals and viticulture through initial approval and two use extensions granted in 2016 and 2017. Further use extensions to allow cereal use have been submitted to the EU Commission for evaluation in 2018. Thus, fungicide usages for the cereals are being evaluated by the EU regulatory assessment organisation, with ESA outcome in 2020 and further discussion at Commission level since. Horsetail extracthas recently been shown to have antibacterial, antifungal, antioxidant, analgesic, anti-inflammatory, antidiabetic, antitumor, cytotoxic and anticonvulsant activities. Initial main field trials to demonstrate its plant protection properties were coordinated in France by the “4P” project “Protection des Plantes Par les Plantes” (Plant Protection by Plants) between 2010 and 2013 but additional field trials were later collected. We detail in this study the results obtained and all the uses of this decoction as a plant protection product. In addition, we describe the full approval processes for the basic substance Equisetum arvense and the extensions of use, covered by the Article 23 of the plant protection regulation in EU.